2020
DOI: 10.1111/mmi.14594
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of AdeABC and AdeIJK efflux pumps elicits specific nonoverlapping transcriptional and phenotypic responses in Acinetobacter baumannii

Abstract: Acinetobacter baumannii is a Gram-negative coccobacillus that can cause a broad range of severe infections, including soft tissue and skin infections, urinary tract infections, and most significantly ventilator-associated pneumonia and bloodstream infections

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 58 publications
2
44
0
Order By: Relevance
“…Furthermore, it is documented that A . baumannii can use other efflux pump-associated genes [ 14 , 65 ] and superfamily [ 22 ] to develop a multidrug-resistance profile. In addition, researchers reported that the AdeABC efflux pump need, in some cases, a synergistic action with other resistance mechanisms to express a level of resistance to particular antibiotic classes [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, it is documented that A . baumannii can use other efflux pump-associated genes [ 14 , 65 ] and superfamily [ 22 ] to develop a multidrug-resistance profile. In addition, researchers reported that the AdeABC efflux pump need, in some cases, a synergistic action with other resistance mechanisms to express a level of resistance to particular antibiotic classes [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Literature supports that it is not just the presence of the AdeABC efflux pump-associated gene but their overexpression triggered by a mutation that induce resistance to antibiotics [15,63,64]. Furthermore, it is documented that A. baumannii can use other efflux pumpassociated genes [14,65] and superfamily [22] to develop a multidrug-resistance profile. In addition, researchers reported that the AdeABC efflux pump need, in some cases, a synergistic action with other resistance mechanisms to express a level of resistance to particular antibiotic classes [67].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The adeABC genes, encoding an RND family transporter, showed a 2–3 log2-fold increase in expression in the presence of any of the four molecules. This apparent induction by polyamines was surprising given that A. baumannii strain AB5075 carries a mutation in the regulator AdeS, which causes constitutive adeABC expression 32 , 33 . The MFS transporter gene amvA was induced by spermidine and spermine but not by putrescine and cadaverine.…”
Section: Resultsmentioning
confidence: 99%